Increased Crime and Decreased Labour Participation in the Income in Mexico - Velázquez Orihuela, Daniel; Lozano Cortes, Rene Leticia (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The growth of crime and the decline of wage share are two trends that have characterized the Mexican economy since the late seventies until the present. However, in the economy research, the causes of these trends are studied in a separated way. In contrast, in this paper is proposed a model of efficiency wages in framework of demand-constrained equilibrium, finding that the growth in the crime supply and the decrease of wage share have a common cause: the diminution of the opportunities for workers to insert themselves and remain employed in the labor market.